Time poverty in Brazil: measurement and analysis of its determinants - Ribeiro, Lilian Lopes; Marinho, Emerson (Estudos Econômicos (São Paulo), 2012)
This article analyzes well-being on an individual level, through the allocation of work hours done by adults and children and thus it measures time poverty in Brazil. In order to achieve such measurement, poverty indicators such as Foster, Greer and Thorbecke (FGT) were adapted into a time poverty mode. Additionally, an analysis of its determinants was also conducted. Among other findings, the fact that women (either children and adult ones) are the time-poorest individuals in urban or rural areas. Another unfortunate finding is that the high rate of time poverty among children, numerically 16,1% is not far from the adult rate which is of 19,7%. The overall composite time poor individual profile is of an African-Brazilian adult woman of little education, not necessarily income poor and residing in an urban area of the northeast region, living in a household of few people, she is the mother of children who are younger than 14 years old.